2013
DOI: 10.1345/aph.1r745
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Argatroban Resistance in a Patient with Elevated Factor VIII Levels

Abstract: With the initiation of argatroban therapy, particular attention should be given to ensure that aPTTs correlate with dosing to prevent life-threatening bleeding complications. Excessive argatroban dosing requirements should prompt further investigation into potential confounders such as elevated factor VIII levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…A recent report showed that elevated factor VIII levels can affect aPTT monitoring of argatroban administration. 26 Modifications of the thrombin time have been proposed for anticoagulation monitoring for many years but have not been widely adopted. One of the first (which used a fibrinogen solution to dilute the patient's plasma) was called the "quantitative thrombin time."…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that elevated factor VIII levels can affect aPTT monitoring of argatroban administration. 26 Modifications of the thrombin time have been proposed for anticoagulation monitoring for many years but have not been widely adopted. One of the first (which used a fibrinogen solution to dilute the patient's plasma) was called the "quantitative thrombin time."…”
Section: Discussionmentioning
confidence: 99%
“…The APTT can be affected by the presence of lupus anticoagulant and low levels of clotting factors, both prolonging the APTT, which will lead to overestimation of drug concentration . Elevated levels of factor VIII can lead to lower‐than‐expected APTT , which could lead to the underestimation of drug effect. Several studies have investigated whether there is a variation in APTT reagent results for known concentration of argatroban: Gosselin et al .…”
Section: Introductionmentioning
confidence: 99%
“…This case shows that in exceptional situations, very high doses of argatroban (up to 19 µg/kg/min in our patient) might be needed to control thrombin generation. A potential explanation could be the massive elevation of factor VIII, which was previously suggested as mechanism in a similar case of argatroban resistance 8. We strongly recommend training staff in the handling of rarely used anticoagulants on a regular basis.…”
Section: Discussionmentioning
confidence: 72%